Ambiente, pueblos indígenas y el momento constitucional - Lanegra, Ivan (2022)
Peru’s independence bicentennial creates a new constitutional moment. As Peru starts its third century as an independent nation, it requires new rules to usher a critical intercultural approach and a strong paradigm of sustainability, from standpoints that respond to the climate crisis and the challenge of the Anthropocene. This article consists of three sections. The first takes stock of the environmental and indigenous issue in the 1993 Constitution. The second raises an agenda in the context of a reform of the Constitution. The third discusses some of the political problems that reform could face, as well as the dangers and opportunities it brings.